English Club Activities to Increase the Nursing Students’ Motivation in Learning English: Students’ Perception - Juliana Juliana (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
The purpose of this study is to determine nursing students' perceptions of English Club activities. This research was conducted at the Kesdam Iskandar Muda Nursing Academy Banda Aceh (AKIMBA) with a sample of 50 students who joined in English Club activities. The data collection method in this study was a questionnaire. The questionnaire was used to find out students' perceptions of English Club activities. The result of this study showed that the average score of student perceptions was 82.3%. It means that students totally agree with the activities of English Club at AKIMBA and it has a very important role in enhancing the nursing students’ interest in English learning. English Club activities can increase the motivation of nursing students in learning. The students feel fun and enthusiastic while gaining the material of the English Club.